A comparison of performance metrics for cloth masks as source control devices for simulated cough and exhalation aerosols. Issue 10 (3rd October 2021) - Lindsley, William G.; Blachere, Francoise M.; Beezhold, Donald H.; Law, Brandon F.; Derk, Raymond C.; Hettick, Justin M.; Woodfork, Karen; Goldsmith, William T.; Harris, James R.; Duling, Matthew G.; Boutin, Brenda; Nurkiewicz, Timothy; et al.
Abstract: Universal mask wearing is recommended to help control the spread of COVID-19. Masks reduce the expulsion of aerosols of respiratory fluids into the environment (called source control) and offer some protection to the wearer. Masks are often characterized using filtration efficiency, airflow resistance, and manikin or human fit factors, which are standard metrics used for personal protective devices. However, none of these metrics are direct measurements of how effectively a mask blocks coughed and exhaled aerosols. We studied the source control performance of 15 cloth masks (face masks, neck gaiters, and bandanas), two medical masks, and two N95 filtering facepiece respirators by measuring their ability to block aerosols ≤7 µm expelled during simulated coughing and exhalation (called source control collection efficiency). These measurements were compared with filtration efficiencies, airflow resistances, and fit factors measured on manikin headforms and humans. Collection efficiencies for the cloth masks ranged from 17% to 71% for coughing and 35% to 66% for exhalation. Filtration efficiencies for the cloth masks ranged from 1.4% to 98%, while the fit factors were 1.3 to 7.4 on headforms and 1.0 to 4.0 on human subjects. The Spearman's rank correlation coefficients between the source control collection efficiencies and the standard metrics ranged from 0.03 to 0.68 and were significant in all but two cases. However, none of the standard metrics were strongly correlated with source control performance. A better understanding of the relationships between source control collection efficiency, filtration efficiency, airflow resistance, and fit factor is needed.